INTERACTIVE LEARNING TECHNOLOGIES IN TEACHING CHEMISTRY AT BUKOVINIAN STATE MEDICAL UNIVERSITY - Yakymchuk, Vira; Kropelnytska, Yulia; Velyka, Alla (SWorldJournal, 2022)
The switch from passive to active education model, when students are able to acquire the knowledge independently and think creatively, is highly important in order to prepare a competitive specialist. Interactive learning technologies are the best choice